Therapeutic hypothermia for the management of hypoxic-ischemic encephalopathy in asphyxiated newborns: Clinical, electrographic and radiologic features of newborns treated at Instituto Materno Perinatal - Medina-Alva, Maria del Pilar (2022)
Hypoxic-ischemic encephalopathy (HIE) is the neurological syndrome caused by perinatal asphyxia. Therapeutic hypothermia (TH) has been shown to reduce HIE-associated morbidity and mortality. A descriptive and retrospective study with 30 newborns with moderate and severe HIE who underwent TH in the Intensive Care Unit (ICU) of Instituto Materno Perinatal, from September 2017 until November 2020. Nine patients were severely affected (30%). The average tome for being admitted in the ICU was at 3.4 hours of life. No important adverse effects attributable to TH were observed. All severely affected patients experienced epileptic crises, and abnormal cerebral ultrasonography and magnetic resonance imaging studies on admission. Mortality was 20.0%, but it was significantly lower in the group with moderate HIE. Clinical, electrographic, and radiological characteristics of neonates with HIE who underwent therapeutic hypothermia were identified. This procedure has been shown to be safe and effective.